2022
DOI: 10.1097/qai.0000000000003018
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Mixed-Methods Examination of Positive Health Check: Implementation Results From a Type 1 Effectiveness-Implementation Hybrid Trial

Abstract: Background: Positive Health Check is an evidence-based video doctor intervention developed for improving the medication adherence, retention in care, and viral load suppression of people with HIV receiving clinical care.Setting: Four HIV primary care clinics within the United States. Methods:As part of a type 1 hybrid trial, a mixed-methods approach was used to longitudinally assess the following 3 key implementation constructs over a 23-month period: innovationvalues fit (ie, the extent to which staff perceiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 65 publications
1
3
0
Order By: Relevance
“…More specifically, both quantitative surveys and qualitative interviews were conducted at baseline and then every 3 months over a 23-month period to collect the eight data time points used to test for statistically significant changes over time in an innovation-values fit measure developed for the PHC intervention (12), a measure of organizational readiness for implementation change developed by Shea et al ( 17) and a measure of implementation climate developed by Jacob et al (18). As recently reported by Garner et al (19) there were not a significant changes over time found for innovation-values fit or organizational readiness for implementing change, but there was significant change over time for implementation climate.…”
Section: Innovative Applications Of the E Ectiveness-implementation H...supporting
confidence: 53%
“…More specifically, both quantitative surveys and qualitative interviews were conducted at baseline and then every 3 months over a 23-month period to collect the eight data time points used to test for statistically significant changes over time in an innovation-values fit measure developed for the PHC intervention (12), a measure of organizational readiness for implementation change developed by Shea et al ( 17) and a measure of implementation climate developed by Jacob et al (18). As recently reported by Garner et al (19) there were not a significant changes over time found for innovation-values fit or organizational readiness for implementing change, but there was significant change over time for implementation climate.…”
Section: Innovative Applications Of the E Ectiveness-implementation H...supporting
confidence: 53%
“…Similar to other hybrid effectiveness-implementation RCTs,98–101 the qualitative assessments will be used to help provide context to the quantitative findings in order to draw conclusions about reach, implementation, acceptability, feasibility and appropriateness of the intervention.…”
Section: Discussionmentioning
confidence: 99%
“…This article presents the effectiveness outcomes. The companion article by Garner et al 17 examines the implementation outcomes that were assessed in this trial.…”
Section: Methodsmentioning
confidence: 99%